The THE ASSOCIATION BETWEEN POOR PERSONAL HYGIENE WITH SOIL-TRANSMITTED HELMINTHS INFECTION AMONG INDIGENOUS (ORANG ASLI) SCHOOLCHILDREN ATTENDING BOARDING SCHOOLS IN SUNGAI SIPUT, PERAK, MALAYSIA - Hassan Basri Jahubar Sathik; Siti Fatimah Kader Maideen; Phei Er Kee; Mohammed A. Abdalqader (Malaysian Journal of Public Health Medicine, 2024)
Soil-transmitted helminths (STH) infection is a global health problem in which poor personal hygiene is a known causative factor. This study aimed to determine the prevalence of STH infection and its association with poor personal hygiene among schoolchildren from indigenous (Orang Asli) communities. A cross-sectional study was conducted in three different boarding schools in Sungai Siput, Perak, Malaysia. A total of 204 schoolchildren (75 boys and 129 girls) were selected as participants via the purposive sampling method. The stool samples were collected and assessed using the Kato-Katz technique, while data on sociodemographic and personal hygiene habits were collected through face-to-face interviews using a pre-test questionnaire. The overall prevalence of STH infection was 47.5% based on different species, including 47.1% of Trichuriasis, 19.6% of Acariasis, and 2.9% of hookworm. Additionally, no association between the sociodemographic characteristics and STH infection was observed. The poor habits of hand hygiene and eating were the key dimensions of personal hygiene that were significantly associated with STH infection with p value <0.001. This study revealed that STH infection is significantly associated (p value <0.001) with poor personal hygiene among the Orang Asli schoolchildren attending boarding schools. In a conclusion, the study found a high prevalence of STH infection among Orang Asli schoolchildren in boarding schools, primarily due to poor hygiene practices such as inadequate handwashing, eating hygiene, geophagy, and limited soap usage. Active interventions such as mass deworming and health education programs are required in these boarding schools.